2017
DOI: 10.1002/2016gc006576
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic records for subduction erosion and subsequent underplating processes revealed by garnet‐staurolite‐muscovite schists in central Qiangtang, Tibet

Abstract: Subduction erosion is confirmed as a crucial geodynamic process of crustal recycling based on geological, geochemical, and geophysical observations at modern convergent plate margins. So far, not a single metamorphic record has been used for constraining a general tectonic evolution for subduction erosion. Here we first revealed metamorphic records for a subduction erosion process based on our study of the Late Paleozoic garnet-staurolite-muscovite schists in the central Qiangtang block, Tibet. Provenance anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
(147 reference statements)
1
22
0
Order By: Relevance
“…On the other hand, the in situ suture model with northward oceanic subduction under the NQB (Li et al, , Li, Chen, et al, , Li, Huang, et al, , ; Zhai, Zhang, et al, , Zhai, Jahn, et al, ; Liang et al, , ; Li et al, ; Wang et al, ) could potentially better explain the late Devonian‐middle Triassic geological evolution in the southern NQB (Figure ), primarily based on the following evidence. First, the Longmu Co‐Shuanghu Tethys Ocean, which once separated the NQB and SQB (Li, ; Li et al, ), was demonstrated to be a diachronous ocean as supported by the continuous Cambrian‐early Triassic (501–242 Ma) ophiolite suites (Fan et al, ; Hu et al, ; Li et al, , Li, Chen, et al, , Li, Huang, et al, , ; Wang, Pan, et al, ; Wu et al, ; Zhai, Jahn, Wang, et al, , ; Zhang et al, ; Zhu et al, ). Second, obvious biota and paleogeography differences have been recently verified across the NQB and the CQMB/SQB.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the in situ suture model with northward oceanic subduction under the NQB (Li et al, , Li, Chen, et al, , Li, Huang, et al, , ; Zhai, Zhang, et al, , Zhai, Jahn, et al, ; Liang et al, , ; Li et al, ; Wang et al, ) could potentially better explain the late Devonian‐middle Triassic geological evolution in the southern NQB (Figure ), primarily based on the following evidence. First, the Longmu Co‐Shuanghu Tethys Ocean, which once separated the NQB and SQB (Li, ; Li et al, ), was demonstrated to be a diachronous ocean as supported by the continuous Cambrian‐early Triassic (501–242 Ma) ophiolite suites (Fan et al, ; Hu et al, ; Li et al, , Li, Chen, et al, , Li, Huang, et al, , ; Wang, Pan, et al, ; Wu et al, ; Zhai, Jahn, Wang, et al, , ; Zhang et al, ; Zhu et al, ). Second, obvious biota and paleogeography differences have been recently verified across the NQB and the CQMB/SQB.…”
Section: Discussionmentioning
confidence: 99%
“…Tectonics 2018). Polyphase foliated clastic rocks mainly consisting of late Carboniferous-Permian submarine siliciclastic flysch Li et al, 1995; surround many other blocks, including Permian-Triassic HP-LT metamorphic rocks (Deng et al, 2000;Kapp et al, 2000Kapp et al, , 2003Li et al, 1995;Li, Zhai, Dong, et al, 2006;Liang et al, 2012Liang et al, , 2017Pullen et al, 2008;Zhao et al, 2014Zhao et al, , 2015Zhang et al, 2017), a late Carboniferous-early Permian gabbro dyke swarm Zhai, Jahn, Su, Ernst, et al, 2013), Paleozoic ophiolite relics Wang, Pan, et al, 2008;Wu et al, 2010;Zhang et al, 2017;Zhu et al, 2006), Permian-early Triassic oceanic island/seamount slices Y. C. Zhang, Shen, et al, 2012), middle-late Triassic abyssal sedimentary rocks (Deng et al, 1996;Li et al, 1997), and Ordovician quartzite and limestone slices (Dong et al, 2011;.…”
Section: 1029/2019tc005589mentioning
confidence: 99%
See 3 more Smart Citations